(untitled) (Research, Society and Development, 2022)
Objective: to understand and analyze the effects of congenital heart disease on the development of a child, as well as to intervene clinically to modify the results of the evaluation. Method: descriptive clinical case study, with quantitative and qualitative analysis of different data of a cardiac child with obstacles in the development process in general and in language acquisition. Procedures and materials used: interview with the child’s mother; recording of the meetings; field diary; application of the Revised Psychoeducational Profile (PEP-R) instrument. Results: a) in the quantitative part: Anaís reached 87 points on the PEP-R development scale, which indicates a neuropsychomotor delay of 01;06 years; b) in the qualitative part: the analysis of fragments transcribed from the videos showed significant differences in Anaís’ responses to the test, before and after the researcher modified her posture during the application. Conclusions: the change of posture of the evaluator sensitive to listening to the subject allowed the emergence of Anaís subjectivity manifested in developing or soon-to-emerge skills. Anaís is at the forefront of the test, to refuse the results obtained in the first application, performed according to the PEP-R manual. As much as some areas remain out of step, the participant showed a transformation in her responses, with the change of approach. Therefore, the test is effective for children with stalemates in language acquisition if the evaluator is not restricted to parameterizing development and clinically intervening in parallel to the evaluation.